Pastoral Family Counseling: Client Center Approach for "Single Mother" at a young age in GMIM Karangetang - Londo, Frisca Elisabeth; Brek, Yohan (MATHESI: Jurnal Pendidikan dan Bimbingan Konseling, 2024)
This research discusses the role of pastoral counseling assistance in helping single mothers or young single mothers face life challenges, especially in the context of the church. Single mothers are often faced with economic problems, social pressure, negative stigma, and complex psychological issues. This condition is exacerbated by their young age, which is often emotionally immature in facing the dual role of mother and head of the family. The Client-Centered approach proposed by Carl Rogers was chosen as a counseling method that emphasizes empathy, support without judgment, and provides space for the counselee to reflect and find their own problem solutions. This research uses a qualitative method with a descriptive approach that emphasizes objective field observations. Through systematic counseling stages, such as establishing trust, data identification, diagnosis, plan development, help implementation, and evaluation, pastoral assistance is expected to run effectively and help single mothers restore their mental and spiritual health.